STAGES OF FORMATION OF INSTITUTIONAL INDEPENDENCE IN THE MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical and methodological foundations of improving the mechanisms of introducing the principles of institutional independence, the ways of improving the mechanisms of introducing the principles of institutional independence based on international standards, the tasks of improving the mechanisms of introducing the principles of institutional independence are studied. Also, current issues of improving the mechanisms of introducing the principles of institutional independence are analyzed.